Valorization of apple tree wood residues by polyphenols extraction: Comparison between conventional and microwave-assisted extraction - Moreira, Manuela M. (2017)
For the first time, the characterization of antioxidant activity and phenolic profile of apple tree (Malus domestica) bark, core and roots was carried out. Phenolic compounds were extracted from the Belgium apple tree wood residues collected at two seasons, namely summer 2015 and winter 2016, using conventional (CE) and microwave-assisted extraction (MAE) techniques. For each extraction technique, the influence of the most important operational parameters, namely solvent composition, extraction time and temperature, on the total phenolic and flavonoid content, and antioxidant activity by the 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity (DPPH-RSA) and ferric reducing activity power (FRAP) assays were optimized. The phenolic profile from the obtained extracts was also characterized by high-performance liquid chromatography with photodiode array detection (HPLC-PDA). Optimum conditions were: 20 mL ethanol:water 60:40 v/v, 20 min, 100 °C, sample weight 0.1 g for MAE and 20 mL ethanol:water 50:50 v/v, 2 h, 55 °C, sample weight 0.5 g for CE. Root extracts obtained by MAE (the most efficient technique) presented the highest phenolic (47.7 ± 0.9 mg gallic acid equivalents/g dry weight) and flavonoid (17.1 ± 0.8 mg epicatechin equivalents/g dry weight) content, and antioxidant activity (28.4 ± 2.0 mg trolox equivalents/g dry weight and 36.1 ± 2.7 mg ascorbic acid equivalents/g dry weight for DPPH-RSA and FRAP assays, respectively), followed by bark and core wood extracts. HPLC-PDA analysis revealed that phloridzin was the main contributor to the phenolic composition representing 52%–87% of the total amount of phenolic compounds quantified, while phenolic acids represents less than 10%. This study reveals the potential of apple tree wood residues valorization through the recovery of phenolic compounds for food, pharmaceutical and cosmetic applications.